Innovative and interactive anatomy learning package: a new learning strategy / Norhayati Liaqat Ali Khan … [et al.] - Liaqat Ali Khan, Norhayati; Abdul Malik, Mohd Maaruf; Razlan, Aimi Nadia; Husin, Andrean (Division of Research and Industry Linkages, 2017)
Teaching and learning anatomy have been a fundamental part of the medical, dental and health science education for decades. The traditional teaching methods now face the challenge of the current generation of Gen Z students, born with a significant reduction in attention span during formal learning period. This forces the lecturers to innovate and revolutionize the teaching methods in anatomy to ensure it remains relevant and interesting. The objectives of this project are to diversify and apply interactive and interesting method of learning anatomy to maintain participation, and to move focus of teaching and learning to the student rather than the lecturer. Students were divided into (i) control group; year two students that were not exposed to this new innovative and interactive practical session and (ii) experimental group; year one students. Experimental group students were instructed to identify, locate, draw and label the skeleton on their colleagues’ body (model). The students presented their artwork and assessed by the lecturers. Result indicated that experimental group students showed their creativity in drawing and labelling on the model. The students could identify the basic structure of the skeleton and differentiate between the types of bone. Another assessment after one week shows that, 85% of students from the experimental group manage to draw and label the skeleton without relying on any teaching and learning aids compared to the control group students (32%). Innovative teaching strategies in Anatomy make the learning process become more interactive. Engagements between students were excellent and coordinated teamwork was shown. Short duration of practical sessions, together with fun activities improved their focus and concentration. This indirectly allows them to remember better and appreciate the knowledge that will be applied in their future.